Strategies for Improving the Performance of Sustainable Domestic Wastewater Treatment Plants - Imtiyaz Olaf Jatmy; Katharina Oginawati (Journal of Social Research, 2023)
The West Java Provincial Government has inaugurated a community-based sanitation program in 18 Bandung Regencies. Especially in the Citarum watershed, domestic waste contributes 68% to river pollution and has water quality status over the past 10 years, showing 54% heavily polluted, 23% moderately polluted, 20% lightly polluted, and only 3% meeting quality standards. Efforts to improve domestic wastewater pollution control require the selection of technology that is influenced by many factors, so a theoretical and practical approach that pays attention to sustainability aspects is needed. Neglasari Village, Banjaran District, Sayati village, Margahayu district, and Cipaku village, Paseh District, are Kcamatan in Bandung Regency who have run the Sanimas program that has not met the muku standards, so it is necessary to improve the performance of the Sanimas wastewater treatment plant that is sustainable. From the location of the S animal wastewater treatment plant spread from the upper reaches of the river, the location of the Sanimas wastewater treatment plant is in a densely populated area and sanitation-prone area, also has the need to deal with sanitation problems. This research was conducted using the SWOT method. A SWOT analysis is performed to obtain recommendations for priority strategies.